Irrigation in the Medieval Islamic Fayyum: Local Control in a Large-Scale Hydraulic System - Rapoport, Yossef (Journal of the economic and social history of the Orient, 2012)
Abstract Because of the unique set of sources available, the Fayyum in Middle Egypt offers a unique case study of large-scale irrigation from antiquity to the Islamic period. A close reading of a cadastral survey of the province from 641/1243-4 shows that the distinctive aspect of the Islamic period was the local control of water supply and management. Drawing on the engineering experience of the villagers, water allocation and management in the gravity-fed canals of the Fayyum were in the hands of iqṭāʿ holders and tribal groups along the main canals, a pattern similar to that which pertained in mediaeval al-Andalus.